Pesan Piagam Madinah dalam Pluralisme di Indonesia - Nurdinah Muhammad (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2011)
Every religion has the truth. The faith to the truth is relied on God as the only source of it. Sociologically, the claim on the it turn to be a religious symbol, which is subjectively understood by a believer. It is no longer concrete and absolute. The plurality of mankind makes the truth become different in discussion and understanding. The difference is caused by various references and backgrounds of believers whose ideal conception turns to be culturally normative. Generally, it motivated religious movements to argue against as they claim that they understood, possessed even has performed the scared value in pure way with all consequence resulted from. As recorded in history, ideas and religious rules inspired an individual or a devoted group the leave the earthly need for reaching higher values and truths. As an ideology and political movement, the pluralism was instantiated by prophet Muhammad to Umar ibn Khattab which was then continued to other khalifahs to unite the divergent groups of religion and various ethics and nation under the system of moderate and tolerant Islamic community that respect the equality of rights and obligations.